Investigating the Impact of Corrective Feedback on Interlingual/Intralingual Grammatical Interference - Mostofi Shalmani, Banafsheh; Pourkalhor, Omid; Safdari, Saeed (Assessment and Practice in Educational Sciences, 2025)
Introduction and Goal: This study examines the efficacy of corrective feedback (CF) types—recasts, elicitation, and metalinguistic feedback—in addressing interlingual (L1-influenced) and intralingual (L2-systemic) grammatical errors among Iranian intermediate EFL learners. Grounded in Richards' (1974) error classification, the research aims to: (1) compare CF effects across gender groups, (2) identify optimal feedback strategies for each interference type, and (3) inform pedagogical practices for error reduction. Methodology: A quasi-experimental design was employed with 90 participants (60 selected via Nelson Proficiency Test, M=25, SD=9) randomly assigned to six groups (three males, three female). Each group received one CF type (recast, elicitation, or metalinguistic) during 10 instructional sessions. Data were collected through pre-/post-tests (Grammaticality Judgment Tests) and analyzed via paired samples t-tests and two-way ANOVA using SPSS 26. Inter-rater reliability was high (Cronbach’s α=0.91). Findings: Recasts significantly improved accuracy (p<0.001) for both genders (male: pretest M=12.33→posttest M=14.03; female: M=12.19→15.05). Metalinguistic feedback showed the highest efficacy (male: M=12.20→15.06, p<0.001; female: M=12.32→14.03, p<0.001), particularly for intralingual errors. Elicitation had moderate effects (male: M=12.30→14.01; female: M=12.34→14.05), with greater impact on interlingual errors. Gender differences were negligible (p>0.05), suggesting universal CF applicability. Conclusion: Metalinguistic feedback emerged as the most effective for grammatical accuracy, likely due to its explicit rule explanation. Recasts enhanced fluency, while elicitation balanced both dimensions. The study confirms CF’s critical role in mitigating L1/L2 interference, with implications for differentiated error correction strategies.